The components and regulation of the Hippo pathway and its relationships with the progression and treatment of Non-small cell lung cancer (NSCLC) - Yuheng Feng; Xueting Gan; Xuezhu Rong; Qiang Han (Cancer Cell International)
Abstract Background Lung cancer is one of the most common malignant tumours, with non-small cell lung cancer (NSCLC) being the predominant type. The morbidity and mortality rates of lung cancer are increasing worldwide. The Hippo signalling pathway is one of the eight classical human cancer signalling pathways, forming a complex signalling network regulated by intracellular and extracellular signals. Under physiological conditions, it plays a crucial role in inhibiting tumor development. Main text Inhibition of the Hippo signalling pathway leads to abnormal activation of its downstream core components, YAP/TAZ, which in turn enhances tumor cell proliferation, invasion, and migration. Recent studies have identified numerous small-molecule inhibitors that target key proteins within the Hippo signalling pathway, which is highly important for the treatment of tumors. Conclusion This paper reviews the activation mechanisms of the Hippo signalling pathway, its crosstalk with other pathways, and potential therapeutic targets to provide new therapeutic avenues.